Brand Positioning Strategy and Consumer Knowledge: Its Impact on Brand Attitude and Purchase Decision - Ruchiat Nugraha, Aat; Fatma Sjoraida, Diah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study analyses the impact of brand positioning strategy and consumer knowledge on brand attitude and purchase decisions. In today’s highly competitive business environment, companies must develop effective marketing strategies to influence consumer attitudes towards brands, ultimately affecting their purchase decisions. Two key factors in this process are precise brand positioning and consumer knowledge of the brands and products they choose. This research employs a quantitative approach with path analysis to identify direct and indirect effects among these variables. Primary data were collected through an online survey distributed to 250 respondents who had purchased electronic products in Indonesia within the past six months. The results of multiple regression analysis indicate that brand positioning (β = 0.52) and consumer knowledge (β = 0.41) significantly influence brand attitude. Additionally, brand attitude significantly affected purchase decisions (β = 0.65). Mediation tests further reveal that brand attitude mediates between brand positioning, consumer knowledge, and purchase decisions. These findings provide valuable insights for companies to design more effective marketing strategies by strengthening brand positioning and enhancing consumer knowledge, ultimately positively impacting purchase decisions. Firms must ensure that these three elements—precise brand positioning, in-depth consumer knowledge, and a positive brand attitude—are well-integrated into their marketing strategies to achieve optimal outcomes.